Outcome of postoperative radiation therapy for cholangiocarcinoma and analysis of dose-volume histogram of remnant liver. Issue 31 (August 2019) - Mukai, Yuki; Matsuyama, Ryusei; Koike, Izumi; Kumamoto, Takafumi; Kaizu, Hisashi; Homma, Yuki; Takano, Shoko; Sawada, Yu; Sugiura, Madoka; Yabushita, Yasuhiro; Ito, Eiko; Sato, Mizuki; et al.
Abstract : Abstract: The aim of this study was to analyze dose-volume histogram (DVH) of the remnant liver for postoperative cholangiocarcinoma (CCA) patients, to find toxicity rates, and to confirm efficacy of postoperative radiation therapy (RT). Thirty-two postoperative CCA patients received partial liver resection and postoperative RT with curative intent. The "liver reduction rate" was calculated by contouring liver volume at computed tomography (CT) just before the surgery and at CT for planning the RT. To evaluate late toxicity, the radiation-induced hepatic toxicity (RIHT) was determined by the common terminology criteria for adverse events toxicity grade of bilirubin, aspartate transaminase, alanine transaminase, alkaline phosphatase, and albumin, and was defined from 3 months after RT until liver metastasis was revealed. The radiation-induced liver disease (RILD) was also evaluated. Tumor stages were distributed as follows: I: 1, II: 8, IIIA: 1, IIIB: 6, IIIC: 14, IVA: 2. Median prescribed total dose was 50 Gy. Median follow-up time was 27 months. Two-year overall survival (OS): 72.4%, disease-free survival: 47.7%, local control: 65.3%, and the median survival time was 40 months. The median "liver reduction rate" was 21%. The OS had statistically significant difference in nodal status ( P  = .032) and "liver reduction rate" >30% ( P  = .016). In the association between the ≥grade 2 RIHT and DVH, there were significantly differences in V30 and V40 ( P  = .041, P  = .034), respectively. The grade ≥2 RIHT rates differ also significantly by sex ( P  = .008). Two patients (6.2%) were suspected of RILD. We suggest that RT for remnant liver should be considered the liver V30, V40 to prevent radiation-induced liver dysfunction. Abstract : Supplemental Digital Content is available in the text